EFEKTIVITAS INOVASI BUMDES DALAM PENINGKATAN EKONOMI MASYARAKAT DESA BINOR KABUPATEN PROBOLINGGO - Amaliyah, Khofifatul; Astuti, Sri Juni Woro; Endarti, Esa Wahyu (MAP (Jurnal Manajemen dan Administrasi Publik), 2023)
This study aims to analyze village-owned enterprises innovation management in improving the economy of the people of Binor Village, Probolinggo Regency and to identify and analyze factors that support village-owned enterprises innovation management in improving the economy of the people of Binor Village, Probolinggo Regency using qualitative analysis methods, The results of the study show that village-owned enterprises innovation management simultaneously has a positive impact and is able to improve the economy of the people of Binor Village, Paiton District, Probolinggo Regency. In addition, the factors driving the innovation management of village-owned enterprises of Binor Village, Paiton District, Probolinggo Regency include competent village-owned enterprises human resources, the application of technology in promoting business for the Binor Village community, and strengthening the synergy of the government, the private sector, and the community.